Validation of the Korean Version of the Body Image Disturbance Questionnaire-Scoliosis. Issue 10 (15th May 2020) - Bae, Seong Ho; Son, Seung Min; Shin, Won Chul; Goh, Tae Sik; Lee, Jung Sub
Abstract : Study Design: Cross-cultural adaptation and validation of the Body Image Disturbance Questionnaire-Scoliosis Objective: The purpose of this study was to evaluate the reliability and validity of an adapted Korean version of the Body Image Disturbance Questionnaire-Scoliosis version (BIDQ-S). Summary of Background Data: A modified version of the BIDQ instrument has been validated in adolescent idiopathic scoliosis (AIS) to assess the perception of spinal appearance and psychological disturbance. However, there is no culturally adapted, reliable, and validated BIDQ-S for the Korean population. Methods: Translation/retranslation of the English version of the BIDQ-S was conducted, and all steps of the cross-cultural adaptation process were performed. The Korean version of the BIDQ-S (K-BIDQ-S) and the previously validated appearance domain of the Korean version of the Scoliosis Research Society-22 Outcomes questionnaire (K-SRS-22) and Spinal Appearance Questionnaire (K-SAQ) were mailed to 152 patients with AIS. Reliability assessments were conducted using κ statistics to assess item agreements, and intraclass correlation coefficients (ICCs) and Cronbach α values were calculated. Convergent validity was evaluated by comparing the scores of the K-BIDQ-S, K-SAQ, and K-SRS-22 appearance domain and discriminant validity by analyzing relationships between K-BIDQ-S score and patient characteristics. Results: All items of the K-BIDQ-S had κ values of agreement >0.6. The K-BIDQ-S showed excellent test/retest reliability with an ICC of 0.912. Internal consistency of the K-BIDQ-S was found to be very good (α = 0.880). Convergent validity testing demonstrated good correlations between the K-BIDQ-S and K-SAQ ( r = 0.617), and between the K-BIDQ-S and K-SRS-22 ( r = −651). The correlation between the K-BIDQ-S and major curve magnitude was significant ( r = 0.688). Discriminant validity was confirmed by significant differences in K-BIDQ-S scores among patients requiring observation, bracing, or surgery. Conclusion: The K-BIDQ-S showed satisfactory reliability and validity, and thus, is considered suitable for the evaluation of spinal deformity appearance in Korean-speaking patients with AIS. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textThe purpose of our study was to translate the Body Image Disturbance Questionnaire-Scoliosis (BIDQ-S) into Korean, to produce a culturally modified version, and to validate this version in the Korean patient cohort. The Korean version of the BIDQ-S showed satisfactory reliability and validity. It is considered suitable for the evaluation of spinal deformity appearance in Korean-speaking patients with AIS.